The Perception of Ancestral History, Legends, and Myths of the Alorese Muslim Minority Group in East Nusa Tenggara, Indonesia - Sulistyono, Yunus; Rahmawati, Laili Etika; Biat, Ismail Tamal; Febrianti, Rika; Zafar, Muhammad; Aprilyana, Niken (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2024)
This paper comprehensively examines the perception of the Alorese about their ancestral history, legends, and myths. It describes the Alorese people's minority status, traces their ancestral lineage, explains the interaction dynamics between coastal and inland residents, moreover unveils their intrinsic legends and myths. The primary data were from oral history interviews conducted among the Alor people in 2018, 2020, and 2022. Through qualitative descriptive methodology, the findings highlight the coexistence of the minority Muslim community with interior inhabitants despite occasional tensions, notably in the area of Pantar Barat. The paper offers a nuanced understanding of the Alorese people's journey, emphasizing their resilient cultural identity amidst broader societal norms. It examines influences shaping Alor society since ancient migrations to modern developments and scrutinizes social dynamics, shedding light on factors influencing social cohesion and cultural continuity. Emphasizing myths and legends as integral to the Alorese culture, the study underscores their role in shaping collective consciousness and identity. In conclusion, it emphasizes the resilience and cultural richness of the Alorese community, calling for further research to deepen understanding and appreciation of their unique heritage.